Preserving the Regional Language through Traditional Culinary Tourism in Tulungagung - Siti Zumrotul Maulida,; Winda Lestari, Oktavia; Qurrotul A’yun, Silfia; Septinaningrum, Septinaningrum (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
Several regional languages in Indonesia have experienced a decline in vitality, some even becoming extinct. Javanese, with the largest number of speakers, could potentially experience the same condition if not maintained sustainably. One factor contributing to the marginalization of Javanese is the growing popularity of imported foods among the millennial generation, which distances them from traditional culinary vocabulary in Javanese. This study aims to examine the role of traditional culinary tourism in sustaining the existence of the Javanese language in Tulungagung. The research employed a qualitative method with an ethnographic approach through field observations, interviews with culinary business owners, and discourse analysis of language use in promotion and interactions among entrepreneurs, tourists, and local communities. The findings reveal that Javanese continues to be consistently used in the naming of traditional foods, transactional communication between sellers and buyers, and culinary history narratives passed on to visitors. The use of Javanese in these contexts strengthens local cultural identity while promoting intergenerational language transmission. The study also identified 22 traditional culinary products that remain preserved, with language practices combining Javanese Krama and Ngoko, as well as code-switching with Indonesian depending on communicative needs. These findings affirm that traditional culinary tourism in Tulungagung not only contributes to the preservation of gastronomic heritage but also serves as a strategic medium for the maintenance and revitalization of the Javanese language in the era of globalization.